2020
DOI: 10.1007/s11417-020-09334-z
|View full text |Cite
|
Sign up to set email alerts
|

Semiformal Organizations and Control During the COVID-19 Crisis in China

Abstract: Scholars often compare China and Western societies in terms of dichotomous forms of control—formal and informal. Recent research indicates a nuanced form of social control—semiformal. Using a survey data collected during the 2020 COVID-19 pandemic in China, this study investigated the prevalence and importance of semiformal organizations, formal organizations, and informal groups participating in social control and social service and the predictors of the perceived importance of these three forms of social con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Previous studies of Chinese disputes or conflict resolutions suggest that forms of mediations are associated with types of disputes (Jiang & Wu, 2015 ; Jiang et al, 2021 ; Michelson, 2007 ). In 1985, Albert Hunter proposed that three levels of social orders—the private, the parochial, and the public—are “arrayed along a continuum of decreasing affect or sentiment” (Hunter, 1985 , p. 232).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies of Chinese disputes or conflict resolutions suggest that forms of mediations are associated with types of disputes (Jiang & Wu, 2015 ; Jiang et al, 2021 ; Michelson, 2007 ). In 1985, Albert Hunter proposed that three levels of social orders—the private, the parochial, and the public—are “arrayed along a continuum of decreasing affect or sentiment” (Hunter, 1985 , p. 232).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only one recent study has been found to quantitatively examine the prevalence and importance of semiformal organizations and control. Based on a survey of 632 respondents, Jiang et al ( 2021 ) investigated semiformal organizations and control during the initial COVID-19 crisis in China. The study compared the prevalence and importance of semiformal organizations, formal organizations, and informal groups participating in six community control and social service activities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…One recipe of China’s success in combating the COVID-19 lies in the emergency management relying on citizens, which is called “mass prevention and defense”, which involved crowds and movement avoidance, health screening, material supplies, sanitization, and information distribution. 24 Therefore, communities as the frontline of the COVID-19 battle represent the most effective defense or the most vulnerable transmission hubs. In addition to fast testing and laborious epidemiological investigation locking down the high-risk areas, most other areas remain unaffected under the grid management enabling rapid responses to the resurgence (see brief comparison in Table 2 ).…”
Section: Analysis From the Risk Governance Perspectivementioning
confidence: 99%